Analisis Resepsi Agen Asuransi Mengenai Gambaran Kerja Keras dalam Video Klip Ardhito Pramono ‘925’ - Alya Jordania; Syaifuddin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Hard work has a correlation with work completion and overcoming various obstacles. This also appeared in Ardhito Pramono's video clip titled "925", where the insurance agent's hard work is depicted in that video. The purpose of this research is to find out how Insurance Agents accept the description of hard work in the Ardhito Pramono video clip "925". The theory used in this research is Encoding- Decoding Theory, with a qualitative approach. The analytical method used in this research is audience reception analysis, with three categories consisting of Dominant Hegemonic, Negotiated, and Oppositional. Based on the results of this research, researchers found that Dominant Hegemonic position is in the side job scene played by Ardhito Pramono. Negotiated position portrayed in hard work of insurance agent in video clip. Meanwhile, there’s an Oppositional position in response to ‘925’ work time. The result of this research also found there are differences of perception regarding the insurance agent's hard work, accordance with the experience of the audience